2017
DOI: 10.1136/bjophthalmol-2017-311254
|View full text |Cite
|
Sign up to set email alerts
|

Ocular findings in Loeys-Dietz syndrome

Abstract: Ocular features of LDS include decreased central corneal thickness and mild myopia. Ectopia lentis may be slightly more common than in controls but appears less common than in Marfan syndrome. Hypertelorism, scleral and retinal vascular abnormalities were not features of LDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 17 publications
2
26
1
Order By: Relevance
“…Mutations in Tgf‐β pathway components, including TGFBR1 (OMIM 190181), TGFBR2 (OMIM 190182), TGFB2 (OMIM 190220) and SMAD3 (OMIM 603190), have been linked to Loeys‐Dietz syndrome, a disorder affecting the connective tissue and cardiovascular systems (Loeys et al, 2005; Loeys et al, 2006). Although craniofacial defects are common in this syndrome, microphthalmia, anophthalmia, and coloboma have not been reported (Busch et al, 2018). Studies utilizing transgenic zebrafish reporter lines show active Tgf‐β signaling in the fissure, and many components of the Tgf‐β signaling pathway are expressed in periocular tissues, including the signaling ligands Tgfb2, Tgfb3, and their receptor Tgfbr2b (Knickmeyer et al, 2018).…”
Section: Ventral Head Mesenchyme and Extracellular Matrix Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in Tgf‐β pathway components, including TGFBR1 (OMIM 190181), TGFBR2 (OMIM 190182), TGFB2 (OMIM 190220) and SMAD3 (OMIM 603190), have been linked to Loeys‐Dietz syndrome, a disorder affecting the connective tissue and cardiovascular systems (Loeys et al, 2005; Loeys et al, 2006). Although craniofacial defects are common in this syndrome, microphthalmia, anophthalmia, and coloboma have not been reported (Busch et al, 2018). Studies utilizing transgenic zebrafish reporter lines show active Tgf‐β signaling in the fissure, and many components of the Tgf‐β signaling pathway are expressed in periocular tissues, including the signaling ligands Tgfb2, Tgfb3, and their receptor Tgfbr2b (Knickmeyer et al, 2018).…”
Section: Ventral Head Mesenchyme and Extracellular Matrix Remodelingmentioning
confidence: 99%
“…(Loeys et al, 2005;Loeys et al, 2006). Although craniofacial defects are common in this syndrome, microphthalmia, anophthalmia, and coloboma have not been reported (Busch et al, 2018). Studies utilizing transgenic zebrafish reporter lines show active Tgf-β signaling in the fissure, and many components of the Tgf-β signaling pathway are expressed in periocular tissues, including the signaling ligands Tgfb2, Tgfb3, and their receptor Tgfbr2b (Knickmeyer et al, 2018).…”
Section: Ventral Head Mesenchyme and Extracellular Matrix Remodelingmentioning
confidence: 99%
“…Loeys-Dietz Syndrome is an AD inherited disorder with mutations in TGF beta receptor 1 (TGFBR1), TGF beta receptor 2 (TGFBR2), TGF beta 2 (TGFB2), TGF beta 3 (TGFB3), or SMAD3 [10,50,66], with an estimated prevalence of ≤1 in 100,000 [51]. Systemic manifestations of LDS are similar to MFS, including vascular aneurysms (cerebral, thoracic, or ab-dominal), skeletal abnormalities (pectus excavatum or carinatum), scoliosis, joint laxity, and craniofacial abnormalities (cleft palate, craniosynostosis, or bifid uvula) [10]. Allergies, skin abnormalities, neurological findings, pulmonary manifestations, and pregnancy-related changes have also been reported [67,68].…”
Section: Loeys-dietz Syndromementioning
confidence: 99%
“…An initial study involving 14 patients with LDS noted 13 with hypertelorism, seven with exotropia, and eight with blue sclera [50]. However, another retrospective review found no patients with hypertelorism or blue/dusky sclera [10], making it challenging to confirm these findings as diagnostic criteria for LDS. Patients with LDS have decreased CCT and increased myopia rates compared to controls, though myopia was less common and severe compared to patients with MFS [10].…”
Section: Loeys-dietz Syndromementioning
confidence: 99%
See 1 more Smart Citation